A Drier Year Markedly Enhances Methane, but Not Carbon Dioxide, Emissions in a Mediterranean Reservoir - Cintia L. Ramón; Isabel Reche; Rodrigo J. Gonçalves; Andrés Martínez‐García; Miriam García‐Alguacil; Sergio López‐Padilla; Javier Herrero; Rafael Morales‐Baquero; Enrique P. Sánchez‐Cañete; Alicia Cortés; Sara Valiente; Francisco J. Rueda (Global Change Biology, 2026)
Reservoirs are increasingly recognized as important sources of greenhouse gases (GHGs), yet the temporal scales and environmental drivers governing CO 2 and CH 4 flux variability remain poorly constrained. This is particularly the case for Mediterranean systems, which are subject to strong hydrological variability. Here, we present and analyze year‐round, high‐frequency eddy covariance measurements of CO 2 and CH 4 fluxes in a Mediterranean reservoir over two years with contrasting hydrological conditions, explicitly evaluating variability at diurnal, multiday, and seasonal timescales. The reservoir acted as a net source of both gases in both years, but CH 4 fluxes exhibited substantially greater temporal variability than CO 2 fluxes. The seasonal component dominated CH 4 flux variability (> 75%), with annual areal fluxes and reservoir‐wide emissions 44% higher during the drier year due to an earlier onset and longer duration of the high‐emission summer period. Near‐sediment temperature and water‐column depth were the primary predictors of seasonal CH 4 emissions, reflecting temperature controls on methanogenesis and hydrological regulation of ebullition. In contrast, CO 2 flux variability was dominated by diel processes, with wind speed emerging as the main predictor of short‐term emissions, while water depth and surface temperature regulated seasonal variability. For both gases, chlorophyll‐a was an important predictor at multiday timescales. Our results demonstrate that the temporal variability of GHG fluxes from Mediterranean reservoirs is highly sensitive to hydrologically mediated changes in lake water levels, particularly for methane. Under climate change, GHG emissions could increase significantly in Mediterranean regions, and potentially in other seasonally dry regions worldwide, as a result of projected trends towards stronger eutrophication and increases in drought frequency and duration. Our study underscores the value of long‐term, high‐frequency observations to improve emission estimates and to better represent reservoir processes in regional and global carbon cycle assessments.

Clinical characteristics, predisposing factors and outcomes for Enterococcus faecalis versus Enterococcus faecium bloodstream infections: a prospective multicentre cohort study - Fenna Scharloo; Francesco Cogliati Dezza; Inmaculada López-Hernández; Pedro María Martínez Pérez-Crespo; Ane Josune Goikoetxea Aguirre; María Teresa Pérez-Rodríguez; Jonathan Fernandez-Suarez; Eva León Jiménez; Miguel Ángel Morán Rodríguez; Isabel Fernández-Natal; José María Reguera Iglesias; Clara Natera Kindelán; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purposes Enterococcal BSI is associated with significant morbidity and mortality, with fatality rates of approximately 20–30%. There are microbiological and clinical differences between E. faecalis and E. faecium infections. The aim of this study was to investigate differences in predisposing factors for E. faecalis and E. faecium BSI and to explore prognostic factors. Methods This study was a post-hoc analysis of PROBAC, a Spanish prospective, multicenter, cohort in 2016–2017. Patients with E. faecalis or E. faecium BSI were eligible. Independent predictors for BSI development in polymicrobial and monomicrobial BSI and in-hospital mortality in the monomicrobial group were identified by logistic regression. Results A total of 431 patients were included. Independent factors associated with E. faecium BSI were previous use of penicillins (aOR 1.99 (95% CI 1.20–3.32)) or carbapenems (2.35 (1.12–4.93)), hospital-acquired BSI (2.58 (1.61–4.12)), and biliary tract source (3.36 (1.84–6.13)), while congestive heart failure (0.51 (0.27–0.97)), cerebrovascular disease (0.45 (0.21–0.98)), and urinary tract source (0.49 (0.26–0.92)) were associated with E. faecalis BSI. Independent prognostic factors for in-hospital mortality in E. faecalis BSI were Charlson Comorbidity Index (1.27 (1.08–1.51)), SOFA score (1.47 (1.24–1.73)), age (1.06 (1.02–1.10)), and urinary/biliary source (0.29 (0.09–0.90)). For E. faecium BSI, only SOFA score (1.34 (1.14–1.58) was associated with in-hospital mortality. Conclusions The factors associated with E. faecium and E. faecalis BSI are different. These variables may be helpful in the suspicion of one or other species for empiric therapeutic decisions and provide valuable information on prognosis.

Water aging and the quality of organic carbon sources drive niche partitioning of the active bathypelagic prokaryotic microbiome - Marta Sebastián; Pablo Sánchez; Guillem Salazar; Xosé A. Álvarez‐Salgado; Isabel Reche; Xosé Anxelu G. Morán; Maria Montserrat Sala; Carlos M. Duarte; Silvia G. Acinas; Josep M. Gasol (Limnology and Oceanography, 2024)
Due to the scarcity of organic matter (OM) sources in the bathypelagic (1000–4000 m depth), prokaryotic metabolism is believed to be concentrated on particles originating from the surface. However, the structure of active bathypelagic prokaryotic communities and how it changes across environmental gradients remains unexplored. Using a combination of 16S rRNA gene and transcripts sequencing, metagenomics, and substrate uptake potential measurements, here we aimed to explore how water masses aging and the quality of OM influence the structure of the active microbiome, and the potential implications for community function. We found that the relative contribution of taxa with a free‐living lifestyle to the active microbiome increased in older water masses that were enriched in recalcitrant OM, suggesting that these prokaryotes may also play a substantial role in the bathypelagic metabolism of vast areas of the ocean. In comparison to particle‐associated prokaryotes, free‐living prokaryotes exhibited lower potential metabolic rates, and harbored a limited number of two‐component sensory systems, suggesting they have less ability to sense and respond to environmental cues. In contrast, particle‐associated prokaryotes carried genes for particle colonization and carbohydrate utilization that were absent in prokaryotes with a free‐living lifestyle. Consistently, we observed that prokaryotic communities inhabiting older waters displayed reduced abilities to colonize particles, and higher capabilities to use complex carbon sources, compared to communities in waters with a higher proportion of labile OM. Our results provide evidence of regionalization of the bathypelagic active prokaryotic microbiome, unveiling a niche partitioning based on the quality of OM.

Assessment of new immobilized photocatalysts based on TiO2 for wastewater decontamination - Alba Hernández-Zanoletty; Oscar Cabezuelo; Agustín París-Reche; Isabel Oller; M. Inmaculada Polo-López; Ana Agüera; Patricia Plaza; M. Luisa Marín; Francisco Boscá; Sixto Malato (Journal of Environmental Chemical Engineering, 2023)

P inputs determine denitrifier abundance explaining dissolved nitrous oxide in reservoirs - Elizabeth León‐Palmero; Rafael Morales‐Baquero; Isabel Reche (Limnology and Oceanography, 2023)
Reservoirs are important sites for nitrogen processing, especially those located in agricultural and urban watersheds. Nitrogen inputs promote N 2 O production and emission, but the microbial pathways controlling N 2 O have been seldom studied in reservoir water columns. We determined N 2 O concentration in the water column of 12 reservoirs during the summer stratification and winter mixing. We explored the potential microbial sources and sinks of N 2 O by quantifying key genes involved in ammonia oxidation (bacterial and archaeal amoA ) and denitrification ( nirS and nosZ ). Dissolved N 2 O varied up to three orders of magnitude (4.7–2441.2 nmol L −1 ) across systems, from undersaturated to supersaturated values (37%–24,174%) depending on reservoirs and depths. N 2 O concentration depended on nitrogen and oxygen availabilities, with the lowest and highest N 2 O values at suboxic conditions. Ammonia‐oxidizing archaea dominated over ammonia‐oxidizing bacteria but were not related to the dissolved N 2 O. In contrast, the abundance of the nirS gene was significantly related to N 2 O concentration, and three orders of magnitude higher than amoA abundance. Denitrifying bacteria appeared consistently in the water column of all reservoirs. The nirS and nosZ genes appeared in oxic and suboxic waters, but they were more abundant in suboxic waters. The nitrate concentration, and nirS and nosZ relative abundances explained the dissolved N 2 O. Besides, nirS abundance was related positively with total phosphorus and cumulative chlorophyll a , a proxy for fresh organic matter. Therefore, P inputs, not just N inputs, promoted N 2 O production by denitrification in the water column of reservoirs.

Patterns of microbial abundance and heterotrophic activity along nitrogen and salinity gradients in coastal wetlands - Gema L. Batanero; Andy J. Green; Juan A. Amat; Marion Vittecoq; Curtis A. Suttle; Isabel Reche (Aquatic Sciences, 2022)
Coastal wetlands are valuable aquatic ecosystems with high biological productivity, which provide services such as a reduction in nitrogen loading into coastal waters and storage of organic carbon acting as carbon dioxide sinks. The predicted rise of sea level or freshwater extractions, particularly in the arid Mediterranean biome, will salinize many coastal wetlands. However, there is considerable uncertainty about how salinization will affect microbial communities and biogeochemical processes. We determined the abundance of total prokaryotes, cyanobacteria, and viruses and quantified the heterotrophic production of prokaryotes sensitive- (predominantly Bacteria) and resistant- (predominantly Archaea) to erythromycin in 112 ponds from nine coastal wetlands. We explored the main drivers of prokaryotic abundance and heterotrophic production using generalized linear models (GLMs). The best GLM, including all the wetlands, indicated that the concentration of total dissolved nitrogen (TDN) positively affected the total abundance of prokaryotes and the heterotrophic erythromycin-resistant (ery-R) production. In contrast, heterotrophic erythromycin-sensitive (ery-S) production was negatively related to TDN. This negative relationship appeared to be mediated by salinity and virus abundance. Heterotrophic ery-S production declined as salinity and virus abundance increased. Consequently, we observed a switch from heterotrophic ery-S production towards ery-R production as salinity and virus abundance increased. Our results imply that microbial activity will change from heterotrophic bacterial-dominated processes to archaeal-dominated processes with anthropogenic nitrogen and salinization increases. However, more studies are required to link the mineralization rates of dissolved nitrogen and organic carbon with specific archaeal taxa to enable more accurate predictions on future scenarios in coastal wetlands.

Major imprint of surface plankton on deep ocean prokaryotic structure and activity - Clara Ruiz‐González; Mireia Mestre; Marta Estrada; Marta Sebastián; Guillem Salazar; Susana Agustí; Enrique Moreno‐Ostos; Isabel Reche; Xosé Antón Álvarez‐Salgado; Xosé Anxelu G. Morán; Carlos M. Duarte; M. Montserrat Sala; et al. (Molecular Ecology, 2020)
Deep ocean microbial communities rely on the organic carbon produced in the sunlit ocean, yet it remains unknown whether surface processes determine the assembly and function of bathypelagic prokaryotes to a larger extent than deep‐sea physicochemical conditions. Here, we explored whether variations in surface phytoplankton assemblages across Atlantic, Pacific and Indian ocean stations can explain structural changes in bathypelagic (ca. 4,000 m) free‐living and particle‐attached prokaryotic communities (characterized through 16S rRNA gene sequencing), as well as changes in prokaryotic activity and dissolved organic matter (DOM) quality. We show that the spatial structuring of prokaryotic communities in the bathypelagic strongly followed variations in the abundances of surface dinoflagellates and ciliates, as well as gradients in surface primary productivity, but were less influenced by bathypelagic physicochemical conditions. Amino acid‐like DOM components in the bathypelagic reflected variations of those components in surface waters, and seemed to control bathypelagic prokaryotic activity. The imprint of surface conditions was more evident in bathypelagic than in shallower mesopelagic (200–1,000 m) communities, suggesting a direct connectivity through fast‐sinking particles that escape mesopelagic transformations. Finally, we identified a pool of endemic deep‐sea prokaryotic taxa (including potentially chemoautotrophic groups) that appear less connected to surface processes than those bathypelagic taxa with a widespread vertical distribution. Our results suggest that surface planktonic communities shape the spatial structure of the bathypelagic microbiome to a larger extent than the local physicochemical environment, likely through determining the nature of the sinking particles and the associated prokaryotes reaching bathypelagic waters.

Variation in transparent exopolymer particles in relation to biological and chemical factors in two contrasting lake districts - Inmaculada de Vicente; Eva Ortega-Retuerta; Ignacio P. Mazuecos; Michael L. Pace; Jonathan J. Cole; Isabel Reche (Aquatic Sciences, 2010)

Viability and potential for immigration of airborne bacteria from Africa that reach high mountain lakes in Europe - Anna Hervàs; Lluís Camarero; Isabel Reche; Emilio O. Casamayor (Environmental Microbiology, 2009)
Summary We have analysed the diversity of the bacteria, which grow after addition of concentrated airborne particles and desert dust in different microcosms combinations with water samples from oligotrophic alpine lakes. We used, on the one hand, airborne bacteria transported by an African dust plume and collected in a high mountain area in the central Pyrenees (Spain). On the other hand, we collected desert dust in Mauritania ( c . 3000 km distance, and a few days estimated airborne journey), a known source region for dust storms in West Africa, which originates many of the dust plumes landing on Europe. In all the dust‐amended treatments we consistently observed bacterial growth of common phyla usually found in freshwater ecosystems, i.e. Alpha ‐, Beta ‐ and Gammaproteobacteria , Actinobacteria , and a few Bacteroidetes , but with different composition based on lake water pretreatment and dust type. Overall, we tentatively split the bacterial community in (i) typical freshwater non‐airborne bacteria, (ii) cosmopolitan long‐distance airborne bacteria, (iii) non‐freshwater low‐distance airborne bacteria, (iv) non‐freshwater long‐distance airborne soil bacteria and (v) freshwater non‐soil airborne bacteria. We identified viable long‐distance airborne bacteria as immigrants in alpine lakes (e.g. Sphingomonas ‐like) but also viable putative airborne pathogens with the potential to grow in remote alpine areas ( Acinetobacter ‐like and Arthrobacter ‐like). Generation of atmospheric aerosols and remote dust deposition is a global process, largely enhanced by perturbations linked to the global change, and high mountain lakes are very convenient worldwide model systems for monitoring global‐scale bacterial dispersion and pathogens entries in remote pristine environments.

Effect of Saharan dust inputs on bacterial activity and community composition in Mediterranean lakes and reservoirs - Isabel Reche; Eva Ortega-Retuerta; Otilia Romera; Elvira Pulido Villena; Rafael Morales Baquero; Emilio O. Casamayor (Limnology and Oceanography, 2009)
We assessed the effects of Saharan dust inputs of particulate matter (PM), total phosphorus (TP), total nitrogen, and water soluble organic carbon (WSOC) on bacterial abundance (BA) in two alpine lakes and two reservoirs in the Mediterranean region. We also experimentally assessed the effects of dust inputs on bacterial activity and community composition and explored the presence of airborne bacteria. We found synchronous BA dynamics at least in one of the study years for each corresponding pair of ecosystems, suggesting an external control. The link between BA dynamics and inputs of PM, WSOC, or TP occurred only in those ecosystems with severe P‐limitation and low dissolved organic carbon. The response was most intense in the most P‐limited ecosystem. Dust addition had a significant positive effect on bacterial growth and abundance, but not on richness, diversity, or composition of the indigenous bacterial assemblages. We also obtained experimental evidence that some airborne bacteria could develop in oligotrophic waters by observing the growth of gamma‐proteobacteria, a group poorly represented in natural aquatic environments.

Evidence of an atmospheric forcing on bacterioplankton and phytoplankton dynamics in a high mountain lake - Elvira Pulido-Villena; Isabel Reche; Rafael Morales-Baquero (Aquatic Sciences, 2008)

Modeled Effects of Dissolved Organic Carbon and Solar Spectra on Photobleaching in Lake Ecosystems - Isabel Reche; Michael L. Pace; Jonathan J. Cole (Ecosystems, 2000)